Redefining education and politics: On the paradoxical relation between two separate spheres. Issue 7 (October 2020) - Vlieghe, Joris; Zamojski, Piotr
In this contribution to the Special Issue on the instrumentalisation of education, we focus on the relation between politics and education, as today there is a dominant discourse on rendering education subservient to the realisation of political aims. Rather than analysing the many ways in which such instrumentalisation takes place, we propose to develop an ontological account that articulates the basic attitude that a political and an educational engagement respectively demand. Our main source of inspiration wasArendt's claim that education should be conceived of as an autonomous and separate sphere, that is, as being meaningful in and of itself, and without any need for an external justification (e.g. in political terms). Taking this standpoint further we will argue that the unique logic of education can be conceived of in terms of unconditional love for the present world. This affirmative attitude is precisely what makes education educational. Conversely, this calls for a redefinition of the logic that -- following Schmitt -- characterises the political, which we will show to be predicated upon a dialectical relation with the world that consists of an attitude of hate towards the present, in view of an ever deferred hoped-for ideal future. This leads us to reconsider the relation that education as an autonomous sphere of human life enters with politics. In order to theorise this kind relation we refer to the idea of pure means, introduced byAgamben .